2020
DOI: 10.1016/j.agwat.2020.106000
|View full text |Cite
|
Sign up to set email alerts
|

Assessing agricultural risk management using historic crop insurance loss data over the ogallala aquifer

Abstract: Much of the agricultural production in the Ogallala Aquifer region relies on groundwater for irrigation. In addition to declining water levels, weather and climate-driven events affect crop yields and revenues. Crop insurance serves as a risk management tool to mitigate these perils. Here, we seek to understand what long-term crop insurance loss data can tell us about agricultural risk management in the Ogallala. We assess patterns and trends in crop insurance loss data from the U.S. Department of Agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We found that one of the top intended future practices was to acquire new agricultural insurance or improve current insurance. Agricultural insurance is one key risk management tool that farmers in the US use to offset climate-related impacts (Claassen et al, 2017;Reyes et al, 2020), but this insurance may not be aligned with needs of farmers, the impacts they face, or their farming systems. On the other hand, it could be that insurance dynamics (e.g., making payments, answering claims, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…We found that one of the top intended future practices was to acquire new agricultural insurance or improve current insurance. Agricultural insurance is one key risk management tool that farmers in the US use to offset climate-related impacts (Claassen et al, 2017;Reyes et al, 2020), but this insurance may not be aligned with needs of farmers, the impacts they face, or their farming systems. On the other hand, it could be that insurance dynamics (e.g., making payments, answering claims, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Drought shock is the key factor that causes rural households to become poor [29]. Some scholars also measured and compared the losses of farmers that were affected by natural risks to agricultural production, such as drought, heat, and hail [30]. Market risk also causes a loss of income for farmers [31,32].…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%
“…Considering that a cotton stand was only successfully established in half of the study years and that in most years heat accumulation will be suboptimal, cotton production poses a relatively large production risk compared with other crops in the region. A high production risk level is also evident from the crop insurance indemnities for the portion of the THP overlying the High Plains Aquifer, 71% of which were attributed to cotton crop failure (Reyes et al, 2020). Cultivar selection for yield was important in every study year, especially at the high irrigation levels.…”
Section: Discussionmentioning
confidence: 99%